Cathepsin D enhances breast cancer invasion and metastasis through promoting hepsin ubiquitin-proteasome degradation. (1st December 2018) - Zhang, Chunyi; Zhang, Mingming; Song, Shushu
Abstract: Hepsin is required for the growth and maintenance of normal morphology, as well as for cell motility and development, initiation of blood coagulation and pro-inflammatory immune response. Here we showed that Cathepsin D (CtsD) as a novel protein is involved in the regulation of hepsin. CtsD destabilizes hepsin by promoting its ubiquitylation and subsequent proteasomal degradation in breast cancer cells. Breast cancer tissue microarray also indicated that hepsin expression was negatively correlated with CtsD by immunohistochemistry. Overexpression of CtsD promoted breast cancer cell migration, invasion and metastasis by enhancing the expression of intercellular cell adhesion molecule-1 (ICAM-1) in vitro and in vivo . These effects were inhibited by ectopic hepsin expression. Taken together, our data reveal a critical CtsD-hepsin signaling axis in migration and metastasis, which may contribute to a better understanding of the function and molecular mechanism in breast cancer progression. Highlights: CtsD destabilized hepsin by promoting its ubiquitylated proteasomal degradation. Hepsin expression was negatively correlated with CtsD in breast cancer TMA. G2E3 targeted hepsin for degradation. CtsD promoted BCC invasion and migration by enhancing the autocrine of ICAM-1. Hepsin expression inhibited BCC invasion and migration induced by CtsD.